The effects of two types of Western diet on the induction of metabolic syndrome and cardiac remodeling in obese rats - Vileigas, Danielle Fernandes [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Corrêa, Camila Renata [UNESP]; Silva, Carol Cristina Vágula de Almeida [UNESP]; de Campos, Dijon Henrique Salomé [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Elsevier, 2021)
Metabolic syndrome (MetS) include obesity as a critical feature and is strongly associated with risk of cardiovascular disease (CVD). Insights into mechanisms involved in the pathophysiology of these clinical manifestations are essential for the development of therapeutic strategies. Thus, Western diets (WD) have been widely employed in diet-induced obesity (DIO) model. However, there are variations in fat and sugar proportions of such diets, making comparisons challenging. We aimed to assess the impact of two types of the WD on metabolic status and cardiac remodeling, to achieve a DIO model that better mimics the human pathogenesis of MetS-induced CVD. Male Wistar rats were distributed into three groups: control diet, Western diet fat (WDF), and Western diet sugar (WDS) for 41 weeks. Metabolic and inflammatory parameters and cardiac changes were characterized. WDF and WDS feeding promoted higher serum triglycerides, glucose intolerance, and insulin resistance, while just WDF presented inflammation in adipose tissue. WDF-fed rats showed increased catalase activity and malondialdehyde (MDA) and carbonyl protein levels, suggesting cardiac oxidative stress, while WDS-fed rats only raised MDA. Both WD equally elevated protein expressions involved in lipid metabolism, but only WDF downregulated the glycolysis pathway. Furthermore, the mechanical myocardial function was impaired in obese rats, being more relevant in WDF. In conclusion, both WD effectively triggered MetS features, although inflammation was detected just on the WDF-fed animals. Moreover, the WDF promoted a more pronounced functional, metabolic, and oxidative cardiac disorder, suggesting to be an adequate model for studying CVD in the scenario of MetS.
Keywords: Cardiac dysfunction; Energy metabolism; High-fat high-sugar diet; Inflammation; Metabolic diseases; Obesity; Oxidative stress